Envisioning the future of territories to tackle demographic and employment challenges in sub-Saharan Africa - Sourisseau, Jean-Michel; Bougnoux, Nathalie; Bélières, Jean-François; Bourgeois, Robin; Soumaré, Mamy; Rasolofo, Patrick (Perspective, 2017)
Version française de l'article In sub-Saharan Africa, the magnitude of the demographic challenge implies anticipating targets to be reached within the time horizon of the next generation, in all sectors of activity. We propose an operational methodology that can be implemented by policymakers and actors in rural territories to envision the future and to prepare their development strategy. This territorial foresight methodology combines an analysis of past local dynamics, a 20-year population projection and a participatory foresight process. It enables collective thinking on sustainable paths and provides a framework for monitoring and steering public territorial action.